Narrative Analysis of Orang Ulu Heirlooms : Uncovering Their Cultural and Historical Significance - Yvonne Michelle, Campbell; Collin, Jerome; Remmy, Gedat; Jamilah, Maliki (Asian Scholars Network (ASNet), 2024)
The narratives associated with family heirlooms often carry deep significance for the families that inherit them. However, due to its portability and despite being passed down through generations, these treasured items are at risk of being lost due to factors such as family conflicts, natural disasters, or even war. This case study examined the heirlooms of three Orang Ulu individuals, focusing on the rich narratives that surround them. The heirlooms discussed include traditional Orang Ulu beaded necklaces, a brass belt, a gold ring, and a set of gongs. Through narrative analysis of in-depth interviews with the participants, the study revealed that each heirloom, inherited from their grandparents, holds a unique story that enhances its sentimental value as well as its cultural and historical significance. These heirlooms, beyond being valuable artifacts, served as living connections to the cultural practices, rituals, and traditions of the Orang Ulu community. The study also underscored the growing commodification of traditional Orang Ulu crafts, particularly beadwork, in the modern market, which may erode their cultural significance. Therefore, safeguarding these heirlooms and their associated narratives is crucial for preserving the cultural identity of the Orang Ulu people.